Annual follow-up of gross diffusive carbon dioxide and methane emissions from a boreal reservoir and two nearby lakes in Québec, Canada - M. Demarty; J. Bastien; A. Tremblay (Biogeosciences, 2011)
Surface water pCO2 and pCH4 measurements were taken in the boreal zone of Québec, Canada, from summer 2006 to summer 2008 in Eastmain 1 reservoir and two nearby lakes. The goal of this follow-up was to evaluate annual greenhouse gas (GHG) emissions, including spring emissions (N.B. gross emissions for reservoir), through flux calculations using the thin boundary layer model. Our measurements underscored the winter CO2 accumulation due to ice cover and the importance of a reliable estimate of spring diffusive emissions as the ice breaks up. We clearly demonstrated that in our systems, diffusive CH4 flux (in terms of CO2 equivalent) were of minor importance in the GHG emissions (without CH4 accumulation under ice), with diffusive CO2 flux generally accounting for more than 95% of the annual diffusive flux. We also noted the extent of spring diffusive CO2 emissions (23% to 52%) in the annual carbon budget.